Смерть і поховальні звичаї та обряди турків - Рухі Ерсой (Народна творчість та етнографія, 2010)
The phenomenon of death occupies very large place in Turkish culture. In daily life it is an important issue, both in the pre-Islamic period and Islamic modern times. This article investigates religious and cultural aspects of death in Turkey: superstitions, signifying and portending death, rites and rituals performing at the time of death, preparation of the dead for its disposal, its burying, and beliefs, rites and rituals related to post-burial customs.